2019
DOI: 10.1155/2019/2573965
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anti-HIV-1 Integrase and Anti-Inflammatory Activities of Compounds from Betula alnoides Buch-Ham

Abstract: Betula alnoides is a medicinal plant in Thai traditional longevity preparations. The crude extracts of this plant possess various biological activities. However, the isolated compounds from this plant have no reports of anti-HIV-1 integrase (IN) activity. Therefore, the present study aims to investigate the anti-HIV-1 integrase and anti-inflammatory effects of isolated compounds from this plant and predict the interaction of compounds with integrase active sites. From the bioassay-guided fractionation of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 47 publications
0
10
0
1
Order By: Relevance
“…Our finding on the anti-HIV activity of these pure compounds is in agreement with previous reports. A report by Chaniad et al [ 61 ] explained the efficacy of betulin (4) as a potent anti-HIV compound with an IC 50 value of 17.7 ± 0.6 μM. Similarly, Esposito et al [ 62 ] reported that lupeol acetate and lupeol inhibited HIV-1 RT-associated RNase H function with IC 50 values of 63 and 11.6 μM, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our finding on the anti-HIV activity of these pure compounds is in agreement with previous reports. A report by Chaniad et al [ 61 ] explained the efficacy of betulin (4) as a potent anti-HIV compound with an IC 50 value of 17.7 ± 0.6 μM. Similarly, Esposito et al [ 62 ] reported that lupeol acetate and lupeol inhibited HIV-1 RT-associated RNase H function with IC 50 values of 63 and 11.6 μM, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…These results are in agreement with previously reported ant-HIV activities of the known compounds. Chaniad et al [ 61 ] described the efficacy of betulin (4) against HIV with an IC 50 value of 17.7 ± 0.6 μM, whereas Esposito et al [ 62 ] reported that lupeol acetate and lupeol inhibited HIV-1 RT-associated RNase H function with IC 50 values of 63 and 11.6 μM, respectively. The current results and the described past anti-HIV effects of compounds found in C. macrostachys , ascertains the importance of the plant, as was previously reported by Maroyi (2017) [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, pellitorine was tested for its inhibitory effect against HIV-1 reverse transcriptase [ 24 ]. In addition, lupeol ( 7 ) and betulin ( 8 ) are known HIV-1 IN inhibitors [ 11 ]. Furthermore, Huang et al, 2007 reported that oleuropein ( 2 ) inhibits HIV-1 IN, but we only observed modest inhibitory effects in the current study, inhibiting 4.7% at 25 μg/mL [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, these drugs have limited clinical benefit because long-term treatments may lead to the emergence of drug resistance and side effects [ 10 ]. Therefore, finding alternative agents that take the pressure away from these more efficient INSTIs will slow the progress of resistance development [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…These polypeptides are then processed by several virus-encoded proteases viz., chymotrypsin like-3CL pro , main protease-M pro -NSp5 and papain like NSP3 proteases into 16 nonstructural proteins (nsps) that constitute the viral replicase-transcriptase system consisting of helicases, RNA-dependent RNA polymerase, and other nonstructural proteins that are packed in membrane vesicles and involved in viral multiplication and assembly [97]. The natural ursolic acid (3β-3hydroxyl-urs-12-ene-28-oic acid, a pentacyclic triterpenoid) and its derivatives present in Hyptis suaveolens and other plants of family Lamiaceae act as potent antiviral agent against rotaviruses, HIV, influenza, and hepatitis B and C viruses [10,53,88,98,99].…”
Section: Hyptis Suaveolens As a Source Of Potential Therapeutic Agentmentioning
confidence: 99%